In situ construction of BiVO4(-)cellulose fibers@CDs(-)polyvinyl alcohol composites for tetracycline photocatalytic degradation - Wang, Tao; Liu, XiQing; Ma, ChangChang; Wei, MaoBin; Huo, PengWei; Yan, YongSheng (Science China. Technological sciences, 2021)
Non-biodegradable and toxic photocatalysts pose as secondary threats to the environmental security. In this work, non-toxic biocomposites were prepared using natural bamboo cellulose fibers (CF), polyvinyl alcohols (PVAs), BiVO 4 , and carbon dots (CDs) from biomaterials. Thereafter, their optical properties, chemical characterizations, and photocatalytic performances were evaluated. The novel BiVO 4 (-)CF@CDs(-)PVA composites were prepared via the combined implementation of in situ and impregnation methods. The optical properties revealed that the CDs and fibers increased the range and intensity of light absorption. The PVAs were used as the shield and dispersant to enhance stability because they have numerous chemical groups. In view of the various possible paths of electron migration, the enhanced photocatalytic activity of BiVO 4 (-)CF@CDs(-)PVA composites for tetracycline degradation was observed under visible light illumination. The origins of the structure, morphology, and optical mechanism in the enhancement of the photocatalytic ability of BiVO 4 (-)CF@CDs(-)PVA composites were discussed and demonstrated.